The Effect of Financial Literacy, Financial Management Behavior, Digital Financial Inclusiveness and Internal Factors on the Sustainability of Micro, Small and Medium Enterprises Participating in the PT PNM Mekaar Financing Program - Syofiatul Aziza Arofani; Adhitya Bayu Suryantara (Indonesian Journal of Business Analytics, 2025)
This study examines influence of financial literacy, financial management, digital financial inclusiveness, and internal factors on the sustainability of MSMEs with a quantitative approach and descriptive method. Data were obtained through questionnaires distributed to PT PNM Mekaar customers with the criteria of Mekaar Plus customers and loans of 8 million and above. So that 232 customers were obtained as research samples. The data were processed with PLS-SEM analysis using SmartPLS 4.0. The results show that financial management and digital financial inclusivity have a good and large impact on MSME sustainability, while financial literacy has no discernible influence on firm sustainability. Internal factors, such as business type and age and financial record keeping, also contribute to MSME sustainability.